Optimization of Lung Scintigraphy in Pregnant Women at The Ottawa Hospital - Golfam, Mohammad (Université d'Ottawa / University of Ottawa, 2017)
INTRODUCTION: Pulmonary embolism (PE) is a major cause of mortality during pregnancy. It is estimated that about 20% of maternal deaths in north america are due to PE. A lung V/Q study in a standard (non-gravid) patient typically consists of a low dosage ventilation study followed by a higher dosage perfusion study. In some centers however, perfusion-only imaging, without accompanying ventilation imaging has been employed. In this method, a several-fold lower dose of radioactivity is used. Perfusion-only imaging has multiple advantages. In addition to reduction of radiation dose to the mother and the fetus, there is decreased cost to the health-care system as well as improved patient convenience and shortened hospital workflow. OBJECTIVES: The present study aimed at assessing the negative predictive value (among other diagnostic accuracy measures) of perfusion-only imaging in a large group of pregnant patients with suspected pulmonary embolism. METHODS: This study was a retrospective cohort study of the entire pregnant patients with suspected PE who underwent V/Q scan at The Ottawa Hospital and their V/Q scans were available in the PACS system. After acquiring REB approval, a comprehensive search in the PACS (Picture Archiving and Communication System) was conducted to find pregnant patients who were assessed for PE in our division since 2004 (the earliest date the V/Q images were available in our system). A statistical consultation was made before the initiation of data collection and at the time of data analysis. All patients who met the inclusion criteria were included. Initially a nuclear medicine resident with 2 years of experience read all the perfusion- only images. The PISAPED criteria were used for image interpretation. Then the results were compared against the reports made by nuclear medicine staffs that were available to us in our electronic system and a final interpretation was made after such comparison. The follow-up clinical notes were used as the gold standard to make a final diagnosis of PE. Finally, diagnostic accuracy measures were calculated. RESULTS: A total of 364 patients were included. Mean maternal age at the time of lung V/Q scan was 30.3 years-old (SD=5.8) ranging from 16 to 51 years-old. From a total of 362 lung perfusion scans, 316/362 (87.3%) scans interpreted as normal, 17/362 (4.7%) scans were interpreted as high probability and 29/362 (8.0%) scans were interpreted as non-diagnostic. Pulmonary embolism was diagnosed in a total of 15 patients directly after performing lung scan. None of the patients with normal perfusion-only scans were diagnosed later with PE, proving a negative predictive value of 100%. The sensitivity and specificity of perfusion-only imaging after including the non-diagnostic studies were 100% (100% to 100%) and 99.1% (88.1% to 94.1%), respectively with a negative predictive value of 100% (100% to 100%) and a positive predictive value of 32.6% (19.1% to 46.2%). Conclusion: The results of the current study show that perfusion-only imaging has a very high negative predictive value for PE in pregnant population and therefore can exclude PE with a very high degree of accuracy.
Keywords: perfusion scan; pregnancy; ventilation scan; lung scintigraphy; pulmonary embolism; PE